Physical activity and healthy eating in the after-school environment - Coleman, Karen J.; Geller, Karly S.; Rosenkranz, Richard R.; Dzewaltowski, David A. (My University, 2011)
BACKGROUND:  No research to date has extensively described moderate and vigorous physical activity (MVPA) and healthful eating (HE) opportunities in the after-school environment. The current study described the quality of the after-school environment for its impact on children’s MVPA and HE. METHODS:  An alliance of 7 elementary schools and Boys and Girls Clubs who worked with the Cooperative Extension Service in Lawrence, KS, was selected to participate in a larger intervention study. After-school settings were observed for information regarding session type, session context, leader behavior, physical activity, and snack quality using validated instruments such as the System for Observing Fitness Instruction Time. Data presented are baseline measures for all sites. RESULTS:  Participating children (n = 144) were primarily non-Hispanic white (60%) and in fourth grade (69%). After-school sites offered 4 different sessions per day (active recreation, academic time, nonactive recreation, and enrichment activities). Children were provided with a daily snack. On 36% of the days observed, this snack included fruit, fruit juice, or vegetables. There was significantly more time spent in MVPA during free play sessions (69%) compared to organized adult-led sessions (51%). There was also significantly more discouragement of physical activity during organized adult-led sessions (29%) as compared to the free play sessions (6%). CONCLUSIONS:  The quality of after-school programs can be improved by providing fruits and vegetables as snacks; offering more free play activities; training the after-school staff in simple, structured games for use in a variety of indoor and outdoor settings; and training after-school staff to promote and model MVPA and HE in and out of the after-school setting.
Keywords: Child and adolescent health; Nutrition and diet; Physical fitness and sport; Community health; Public health